Acute bilateral anterior tibial compartment syndrome after Caesarian section in a diabetic. Issue 1 (January 1980) - Lecky, B
Abstract : An acute bilateral anterior tibial compartment syndrome is described in a young diabetic after Caesarian section with subsequent recovery. A vascular aetiology appears most likely.